"O tym cały pociąg szeptał, mruczał i mamrotał". Akuzmatyka Pierre'a Schaeffera i jej radiowe realizacje - Łastowiecki, Janusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article is railway as a musicological concept. The motif of trains and train travel becomes present in audiophile listening as a set of specific sounds as well as altered ones in the mastering process. I am going to analyse the pioneering experiments of Pierre Schaeffer and the radio works by Eugeniusz Rudnik, as well as railway-related audio concepts used in the adaptations of works by Bruno Schulz (The Hourglass Sanatorium), Vasily Grossman (Everything flows), Edward Stachura (Fabula rasa and Siekierezada), Stanisław Ignacy Witkiewicz (The Crazy Locomotive) and Tadeusz Konwicki (The Salto). Typomorphology shall be applied in the analysis of the abovementioned plays. This perspective allows to decipher the sound metaphors accurately and also to analyze the individual sounds making up the soundscape.
Keywords: typomorfologia; odbiór audiofilski; ambient; pejzaż dźwiękowy; przedmiot dźwiękowy; typomorfology; audiophile reception; soundscape; sound object